Exiled : from the killing fields of Cambodia to California and back - Cengel, Katya (Potomac Books, an imprint of the University of Nebraska Press, 2018)
"The story of four families confronting deportation forty years after the beginning of large-scale resettlement of Southeast Asian refugees in America"--